Development of nano-activated carbon and apply it for dyes removal from water. Issue 1 (28th October 2021) - Al Jebur, Layla A.; Alwan, Liqaa Hussein
Abstract: The present study investigates the production of nano-activated carbon from banana peels mixed with nylon 6.6 and polyethene. The carbonization process was carried out by mixing accurate percentages of the banana peels with different ratios of nylon 66 and a suitable amount of potassium hydroxide. The fusion carbonization, without solvents, was used in this paper to decompose the nylon mixture, releasing amino and carboxylate roots that can easily react with the carbon chains. The prepared nano-activated carbon was characterized using different technologies, including SEM, AFM, FT-IR, and EDX technologies. The results showed the produced carbon has spherical particles with a pore size of 1.21 nm and a surface area of 1, 071.7 m 2 /gm. Additionally, it was noticed, from the FT-IR spectrum, the prepared carbon does not contain any active groups, which means it is an inert material. X-ray analysis showed the new carbon is made from carbon (78.57%) and oxygen (21.43%). After optimizing the wavelength, the prepared carbon was used to adsorb methylene blue and Eirochrom black T dyes from solutions. The results showed the best equilibrium time, dose of carbon and concentration of dyes was 40–50 minutes, 0.04 g and 20 ppm, respectively. HIGHLIGHTS: Nano-activated carbon was made from banana peels, nylon 6.6 and polyethene. The new carbon has a surface area of 1071.7 m 2 /gm. Nano-activated carbon removed dye after 40–50 minutes. Graphical Abstract